Some Issues of Education of Students in Need of Help (European Journal of Pedagogical Initiatives and Educational Practices, 2023)
Social problems in child education today; attacks on mobile phones and social networks are on the rise. While these modern means of communication are important means of communication, they have a negative effect on some spiritually immature young people. Parents, together with educational institutions, should explain the true nature of communication tools to young people who have fallen under the influence of social networks.